The Influence of Employee Work Ability and Quality of Public Service On Community Satisfaction - Geby Riskina; Yusnaidi Yusnaidi (Ridwan Institute, 2021)
The Samatiga District Head Office is a government agency whose job is to provide convenience for the community in managing local government, this government agency was established to provide services to the community. The purpose of this research is to find out how much influence the work ability of employees and the quality of public services have on community satisfaction. The location of this research was conducted at the Samatiga District Head Office. The research sample studied was 100 people, from a total population of 15, 688 people. Sampling was done by means of a random sample method. The sample was selected according to the criteria related to the study. The results obtained from the R test results obtained that the value of the X variable can affect the Y variable by 5.75% and from the linear regression equation on the t test, namely Y=7.271+0.123X1+0.501X2. The results of the f test of the work ability variable X1, the variable quality of public services X2 are simultaneously related to the variable of community satisfaction (Y). With a significant level < than 0.05